2021
DOI: 10.1007/s40257-021-00631-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Effects of Vitiligo: A Systematic Literature Review

Abstract: Background Patients with vitiligo experience reduced quality of life. Objective To comprehensively describe the available evidence for psychosocial burden in vitiligo. Methods A systematic review of observational studies and clinical trials identified using PubMed, EMBASE, Scopus, and the Cochrane databases was performed through 1 March, 2021, to assess psychosocial comorbidities in vitiligo. Two independent reviewers performed an assessment of articles and extracted data for qualitative synthesis. Results Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
112
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 165 publications
(518 reference statements)
4
112
1
7
Order By: Relevance
“… 18 Importantly, the quality of life of vitiligo may be largely affected by psychosocial comorbidity. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Importantly, the quality of life of vitiligo may be largely affected by psychosocial comorbidity. 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 Importantly, the quality of life of vitiligo may be largely affected by psychosocial comorbidity. 19 Skin plays an important role in our interaction with the world, and skin color is an important factor in perceiving someone's health. 20 The results of our study showed that the total score of SCL-90 was 136.44, which is significantly higher than the Chinese norm.…”
Section: Discussionmentioning
confidence: 99%
“…Although vitiligo will not bring serious health problems, it could cause significant cosmetic problems and serious psychological damage to patients ( Simons et al, 2020 ). The psychological burden of this skin disease is relatively high ( Ezzedine et al, 2021 ). Patients with vitiligo are more likely to suffer clinical depression or depressive symptoms ( Lai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the non-symptomatic whitish macules on skin in vitiligo patients are not as onerous as the signs of other chronic cutaneous diseases. Nevertheless, vitiligo may serve as a cause for the wide range of psychological impairments resulting in violation of mental well-being and quality of life [4][5][6]. To this end, the better understanding of pathophysiology of vitiligo might be achieved by investigation of the interplay between genetic, neurohumoral, and environmental factors in the onset and progression of the disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%